More gene manipulations in fungi - Alic, Margaret; Bennett, J. W.; Lasure, Linda L. (Academic Press, 1991)
The original work, published in 1985, appeared at the first interface between classical fungal genetics and modern genetic engineering, reflecting the excitement of a young and promising discipline. Since then, molecular mycology has come of age. The entirely new More Gene Manipulations in Fungi reviews state-of-the-art research with an intent to inform the researcher about what can be achieved by studying fungal systems with the tools of molecular biology. This book is a current reference providing overviews as well as practical information. Updates Bennett and Lasure's classic Gene Manipulations in Fungi published in 1985**Describes fungi for the study of fundamental problems in biology and biochemistry**Explains both classical and molecular genetics for the study of fungi**Contains special appendixes on genetic analysis, growth media, and coding conventions**Demonstrates the progress of molecular mycology since the seminal paper published by Beadle and Tatum in 1941.